2018
DOI: 10.12669/pjms.345.16026
|View full text |Cite
|
Sign up to set email alerts
|

Shift work disorder and its related factors among health-care workers in a Tertiary Care Hospital in Bangalore, India

Abstract: Background & Objective:Shift work disorder is the presence of excessive day time sleepiness and insomnia affecting people whose work hours overlap with the typical sleep period. Shift work has pronounced effect on physical and mental health of an individual. Our objective was to estimate the prevalence of symptoms of shift work disorder and the factors associated with it among hospital staff in a tertiary care hospital in Bangalore, India.Methods:This cross-sectional study was conducted at a private teaching t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 15 publications
6
17
1
2
Order By: Relevance
“…Eight studies (Cotrim et al, 2017; Dorrian et al, 2011; Ferguson et al, 2010; Ferri et al, 2016; Harma et al, 2018; Heath et al, 2016; Korompeli et al, 2014; Verma et al, 2017) measured fatigue between the time of shift where it was revealed that the night shift has more cases and reports of fatigue among shift workers than day shifts or afternoon shifts. Five studies (Barker & Nussbaum, 2011; Choobineh et al, 2018; Dorrian et al, 2011; Matthew et al, 2018; Patterson et al, 2015) concluded that fatigue score was higher when shift duration and working hours were longer. Three studies (Dorrian et al, 2011; Lu et al, 2017; Mehta et al, 2017) found that workers with heavier workload reported more cases of fatigue when compared with workers with a lighter workload.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies (Cotrim et al, 2017; Dorrian et al, 2011; Ferguson et al, 2010; Ferri et al, 2016; Harma et al, 2018; Heath et al, 2016; Korompeli et al, 2014; Verma et al, 2017) measured fatigue between the time of shift where it was revealed that the night shift has more cases and reports of fatigue among shift workers than day shifts or afternoon shifts. Five studies (Barker & Nussbaum, 2011; Choobineh et al, 2018; Dorrian et al, 2011; Matthew et al, 2018; Patterson et al, 2015) concluded that fatigue score was higher when shift duration and working hours were longer. Three studies (Dorrian et al, 2011; Lu et al, 2017; Mehta et al, 2017) found that workers with heavier workload reported more cases of fatigue when compared with workers with a lighter workload.…”
Section: Resultsmentioning
confidence: 99%
“…This support should focus on strategies to mitigate the increased risk of burnout, job dissatisfaction, and absences that are associated with fatigue in healthcare providers. (66) Building positive work cultures leads to an environment that can mitigate fatigue risk in the paramedic work environment. As this trust is built and matured; the system can engage staff in discussion that identifies cultural safety nets that can be formalized and areas identified for improvement, further building towards an environment of self-reporting and self-identification of hazards, risks and proactive prevention through cooperation.…”
Section: Resultsmentioning
confidence: 99%
“…A weekly workload equal to or greater than 45 hours increased 2-3 times the chance of sleepiness. An 8-hour/day workday increased the chance of sleepiness both in a study conducted in Thailand 14 and in India 11 . The systematic review by Linton et al (2015) 34 was not able to determine the effect of workload on sleep disorders, as this condition can be evaluated using several methods, which may show distinct outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of sleepiness in nursing professionals worldwide varies between 2.8% in India 11 and 53% in Nigeria 12 . Excessive somnolence can be the result of a chronic condition of difficulty initiating and maintaining sleep, in addition to a reduction in its duration due to conflicting circadian rhythms, particularly the sleep-wake cycle 13 .…”
Section: Introductionmentioning
confidence: 99%